Biomass (Biovolume) of Periphyton in the Salo River Kampar District Riau Province - Hosianna Sitorus; Asmika H. Simarmata; Madju Siagian (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Periphyton is a group of microorganism that grow in some natural substrates such as rock, wood, plants and aquatic animals. A research aims to understand the biomass of periphyton in the Salo river based on its biovolume has been carried out in April-May 2015. There were 3 stations namely the upstream (S1), midstream (S2), and downstream (S3) of the river. Samplings are conducted 4 times, once/ week. Results shown that the biomass of the periphyton in the S1 was 9.43 mg/cm2, S2 was 14.63 mg/cm2 and S3 was 51.32 mg/cm2. The abudance of periphyton in the all station Salo River is significantly different, there were S1 (9.43 mg/cm2), S2 (14.63 mg/cm2), and S3 (51.32 mg/cm2). Periphyton biomass in the Salo River in general was around 9.43 -51.32 mg/cm2.Keywords: Periphyton, biomass (biovolume), Water Quality, Salo River